Efficacy of Five Organic Acids Combination on T2- Mycotoxicosis in Rats - Ammar A. Fadhil; Suhair Hassan Alkutbi; Eman S. Nassir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Mycotoxins are secondary by-products of mold metabolism and are accountable for human and animal mycotoxicosis. The most serious trichothecenic mycotoxin is the fungal T-2 mycotoxin. T-2 mycotoxin impaired nutrient absorption, metabolism, and then, eliciting severe oxidoreductive stress. Diet plays a key role beyond the supply of nutrients in order to promote animal and human health. Organic acids have been commonly used to exert antioxidative stress capacity in the liver and gut ecosystem. This study is planned to explore, the competence of using (X-MoldCid®) during chronic T-2 mycotoxicosis course in rat. Rats were allocated into 4 main groups, (CN-Gr), negative control and was allowed for the free access to the normal rats chow and the tap water for 90 days. (OAC-Gr), which was assigned as the organic acids positive control and was allowed for the free access to normal rat chow and (X-MoldCid®) in the tap water for 90 days .Group 3 or (T2-Gr) and was given the T2 contaminated chow ad libitum and group 4 (T2+OAC-Gr) .Each one of the four groups was subdivided into two subgroups (n=7) that one was sacrificed on day 45 (Subgroup A) meantime the remaining rats (Subgroup B) maintained until finishing of the entire study period (90 days). In T2 intoxicated group, liver histopathological findings revealed, lesions of reversible types (hydropic and fatty degenerations) while intestinal histopathological findings revealed, lesions of hyperactive goblet cells with sever slaughing of epithelia. In T2+OAC-Gr, the ultimate efficacy of organic acids success in limiting the apoptotic activity and preventing hepatic necroinflammatory changes which were in accordance with the improvement of antioxidative status, liver and intestinal function enzymes and other serum biochemical estimated tests. The total results of this study have been clarified the regenerative and antioxidant potentials of (X-MoldCid®) in coping with T2-toxin mediated intestinal lesions and hepatotoxicityin rats.